Undergraduates and intercultural communication competence: Creating a plan for performance - Madlock, A. (International Journal of Learning, 2009)
Some studies indicate that students develop intercultural communication competence through interaction in multicultural classrooms. However, what happens when classrooms are predominately homogenous and student exposure to other cultures is limited to media representations? It is not uncommon to find this situation still existing on some college campuses in the United States of America, where students have never come in contact with individuals different from themselves, beyond service industry workers, if any contact is made at all. The idea of establishing a significant relationship with someone culturally different is not given any thought. As an instructor of color how does one get students to move beyond their comfort zone and take action to meet individuals that are culturally different outside of the classroom? This paper describes the results of a textual analysis using grounded theory of student writing as they reflect on how to develop and implement effective communication strategies with individuals culturally and ethnically different from themselves outside of the classroom. The results of which might also be used to transform thinking about the diverse community surrounding the university and influence future decision-making on issues of social justice and human equality. © Common Ground, Annette Madlock.
Keywords: Grounded theory; Intercultural communication Competence; Multicultural classroom; Textual analysis; Undergraduates; dept.com; ⛔ No DOI found

Saladin and the truth of religion in Decameron I. 3 and X. 9 - Rhodes, J. (Through a Classical Eye: Transcultural and Transhistorical Visions in Medieval Engl. Italian, and Latin Literature in Honour of Winthrop Wetherbee, 2009)
Journal Abbreviation: Through a Classical Eye: Transcultural and Transhistorical Visions in Medieval Engl. Italian, and Latin Literature in Honour of Winthrop Wetherbee
Keywords: dept.eng